Young people's engagement with climate change issues through digital media – a content analysis. Issue 1 (13th December 2021) - Parry, Sarah; McCarthy, Sofi Rose; Clark, Jennie
Abstract : Background: The reporting of climate change issues through social media can influence young people's mental health and engagement. However, there has been little research undertaken directly with young people in relation to social and digital media's reporting of climate change, and how this is experienced by young people. Method: This study aimed to explore the interface between climate change and social media reporting for young people. A two‐stage iterative approach to recruitment and data collection included an initial qualitative stage ( N = 28), consisting of open‐ended questions about social media's reporting of climate change issues. The second stage ( N = 23) included further open‐ended questions and 10 Likert‐Scale questions. Overall, 51 young people 16–25‐years‐old opted to take part (M = 11; F = 40). Descriptive statistics and an inductive data‐driven content analysis are reported. Results: Overall, 95% of the participants reported that they had the personal skills to cope with climate change reporting on social media. Most participants stated that coverage on the climate increased 'climate change anxiety' but not their overall mental health difficulties. A four‐stage experiential process of observing social media's reporting of climate change, feeling emotionally affected by the reporting, critically apprising the content and feeling motivated to engage in climate change activism emerged from the content analysis. The participants discussed experiences of digital media, rather than solely social media, in their accounts. Conclusions: The participants recommended changes to climate change reporting and increasing access to education about climate change issues to reduce anxiety and enhance motivation for positive personal engagement. Involving young people in conversations and education about climate change were seen as protective factors for mental health and enablers for motivation. Motivation, agency and pathways for positive change were associated with hopefulness.